The Norton anthology of English literature : (Norton & Company, 2001)
With adoptions at over 1,300 colleges and universities in its first semester; the Seventh Edition of The Norton Anthology of English Literature continues to be the indispensable anthology. Like its predecessors, the Seventh Edition offers the best in English literature from the classic to the contemporary in a readable, teachable format. More selections by women and twentieth-century writers, a richer offering of contextual writings and apparatus fully revised to reflect today's scholarship make the Seventh Edition the choice for breadth, depth, and quality. For the first time ever, the acclaimed Norton Anthology of English Literature is available in six separate volumes, each of which cover a specific period of English lit and focus on the wide range of writers and literature, with full annotation and commentary. Adapted unabridged from the full Norton Anthology, this volume is ideal for focused study or specific coursework in the period.